Quantum Theory of X-ray Radiation by Relativistic Electrons at Small-Angle Reflection from Crystals; Journal of Instrumentation; Vol. 13 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-17) - Korotchenko K. B. Konstantin Borisovich (2018, 2018)
Title screen